Multifunctional nanoparticles for targeting the tumor microenvironment to improve synergistic drug combinations and cancer treatment effects. Issue 45 (28th October 2020) - Chen, Mei-Lin; Lai, Chih-Jen; Lin, Yi-Nan; Huang, Chien-Ming; Lin, Yu-Hsin
Abstract : Nanoparticles can internalize into cancer cells through CD44 and P-selectin ligand recognition, leading to significant enhancement of anti-prostate tumor activity. Abstract : Docetaxel-based chemotherapy for prostate cancer is the clinical standard of care. However, nonspecific targeting, multiple drug resistance, and adverse side effects are common obstacles. Various natural compounds, including epigallocatechin-3-gallate (EGCG) in combination with taxane, have the potential to be developed as anticancer therapeutics. Although synergistic hydrophobic–hydrophilic combination drugs have been used with some success, the main drawbacks of this approach are poor bioavailability, unfavorable pharmacokinetics, and low tissue distribution. To improve their synergistic effect and overcome limitations, we encapsulated EGCG and low-dose docetaxel within TPGS-conjugated hyaluronic acid and fucoidan-based nanoparticles. This approach might facilitate simultaneous target-specific markers at the edge and center of the tumor and then might increase intratumoral drug accumulation. Additionally, the successful release of bioactive combination drugs was regulated by the pH-sensitive nanoparticles and internalization into prostate cancer cells through CD44 and P-selectin ligand recognition, and the inhibition of cell growth via induced G2/M phase cell cycle arrest was observed in in vitro study. In in vivo studies, treatment with cancer-targeted combination drug-loaded nanoparticles significantly attenuated tumor growth and increased M30 protein expression without causing organ damage. Overall, the multifunctional nanoparticle system improved the drugs' synergistic effect, indicating great potential in its development as a prostate cancer treatment.